Pharyngeal reconstruction after total laryngectomy with sliding epiglottis: technical aspects with retrospective review - Grošelj, Aleš; Tancer, Ivana; Jerman, Anže; Paučič, Jošt; Pušnik, Luka (Frontiers in Oncology, 2024)
Introduction: Several techniques have been employed for defect reconstruction after total laryngectomy, among others sliding epiglottoplasty. As there is a paucity of data on sliding epiglottoplasty after total laryngectomy, this study aimed to present this reconstruction technique in detail with the retrospective analysis of the patients. Methods: We retrospectively reviewed single-center medical records of patients who underwent pharyngeal reconstruction after total laryngectomy between 2007-2013, with a follow-up to 2020. The study included patients who had total laryngectomy performed followed by a primary closure or sliding epiglottoplasty. The patients were divided according to the pharyngeal reconstruction technique: sliding epiglottis (n = 38) and primary closure (n = 120). Results: The baseline characteristics of patients, TNM stages, and previous treatment strategies did not differ significantly between the sliding epiglottis and primary closure group. The postoperative complication rates, including the pharyngocutaneous fistulae formation and strictures were comparable between the analyzed groups; however, a slightly higher incidence of pharyngocutaneus fistulae was noted within the patients after sliding epiglottoplasty. Overall 3-year survival of patients who underwent the epiglottoplasty and primary closure group were 73.7 % vs. 57.5 %, respectively. Conclusions: Sliding epiglottoplasty is considered a safe reconstruction technique. Although slightly better outcomes were noted within the epiglottoplasty group, it is still considered inferior to the primary closure. This technique ought to be considered in meticulously selected patients in whom primary closure is not feasible, epiglottis with nearby structures is spared from disease, and when the distal flaps are less appropriate or contraindicated.